Ecological Virtues in Laudato Si’ - Kureethadam, Joshtrom Isaac (ETHICS IN PROGRESS, 2016)
Laudato Si’, Pope Francis’ recent encyclical on care for our common home, invites humanity to cultivate “ecological virtues” in order to become more responsible stewards of our imperilled common home. According to the Pope, the formation of healthy habitus for the stewardship of Earth can be achieved only through the cultivation of appropriate ecological virtues. It may be recalled that there is a growing awareness of the importance of the role of ecological virtues in environmental ethics today. In this paper we shall reflect on seven ecological virtues: praise, gratitude, care, justice, work, sobriety, and humility. They do not receive a separate treatment in Laudato Si’, but are mentioned throughout the encyclical. They are like signposts that indicate the road that we need to travel in caring for our common planetary home.